The writing abilities of juvenile justice youths: A confirmatory factor analysis. Issue 6 (24th November 2020) - Rodgers, Derek B.; Reed, Deborah K.; Houchins, David E.; Aloe, Ariel M.
Abstract: To better understand the writing skills of juvenile offenders and the components of their writing abilities, this study explored extant data from six measures of adolescents' writing skills administered upon their entrance into a juvenile justice facility. Overall, the 235 students (ages 13–16; Grades 5–11) exhibited low scores on all writing measures, but there was a wide range in their performance with some students scoring at or near ceiling. A confirmatory factor analysis supported our hypothesis of a two-factor structure consisting of sentence-level and discourse-level skills. We compared the fit of three alternative models: a one-factor model, a higher-order model, and a bifactor model. None of the alternative models was superior to the two-factor model. These factors provide empirical support for certain aspects of traditional writing models and suggest a framework for efficiently assessing students to inform instruction.